A previous hemorrhagic stroke protects against a subsequent stroke via microglia alternative polarization - Shin-Shin Lee; Li Pang; Yin Cheng; Jia Xin Liu; Anson Cho Kiu Ng; Gilberto Ka Kit Leung (Communications Biology, 2022)
Microglia shift in polarization from an M1 to a M2 phenotype following a past “mini” stroke, resulting in better neurological function recovery, faster attenuation of lesion volume, and better survival.